Experience of Persistent Gestation Trophoblastic Disease in a Tertiary Medical College Hospital, Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objectives: To study the clinical presentation and risk factors of persistent trophoblastic disease and its outcome of treatment with chemotherapy.Materials and methods: This observational study was carried out on fifty patients of persistent trophoblastic disease who were admitted in the Department of Obstetrics & Gynaecology, Mymensingh Medical Hospital (MMCH) during one year period. Evaluation of disease was done by thorough clinical examination and a set of investigations including chest radiography, ultrasound scan of abdomen and pelvis and estimation of serum â hCG. The four factors under analysis of PTD were age of the patient, clinical presentation, gestational age at diagnosis of molar pregnancy and nature of antecedent pregnancy. Patients with non-metastatic trophoblastic disease and low risk metastatic trophoblastic disease were offered single agent chemotherapy with methotrexate and folinic acid rescue in consultation with the oncologist. When â hCG response was inadequate, multi-agent chemotherapy was given. Complications of chemotherapy were also observed and supportive treatment was given.Results: Out of 50 patients, 49 (98%) patients had antecedent molar pregnancy and 1(2%) had missed abortion. In cases of post molar trophoblastic disease, 28 (57.58%) were in 20-30 yrs. Mean ± SD was 31.35 ± 7.25. In these cases gestational size of molar pregnancy was between 16-20 weeks in 24 (48.98%), 20 wks in 6 (12.24%) cases. Mean ± SD was 16.78 ± 4.45 wks (p